A Theoretical Framework for Service Life Prediction of Reinforced Concrete Structures in Chloride Environment using Load Factors - Pathan, A. A.; Khaskheli, G. B.; Qureshi, A. S. (Engineering, Technology & Applied Science Research, 2021)
Service life modeling of reinforced concrete structures in a chloride environment is mainly performed without considering the loading effects. Different loading effects can produce different service life results. This study presents a theoretical framework for the modeling of the service life of reinforced concrete structures in a chloride environment using loading factors, showing that, depending on the loading nature (either compression or tension), different diffusion results could be obtained. This paper also highlights various approaches to service life modeling, such as the deterministic, probabilistic, and semi-probabilistic, which consider different ways to estimate the service life of reinforced concrete structures in chloride environments. The importance of various distributions for the input parameters in the chloride ingress modeling was examined. The proposed framework includes a procedure to estimate the probability of concrete failure in chloride environments.